Cell membrane permeable fluorescent perylene bisimide derivatives for cell lysosome imaging. Issue 87 (5th September 2016) - Zhang, Shuchen; Duan, Wenfeng; Xi, Yanan; Yang, Tao; Gao, Baoxiang
Abstract : The cellular uptake of Lyso-APBI probes is improved by PEG chains, and the double morpholine moieties make Lyso-APBI probes have higher acid activation ratio and better cell lysosome specificity. Abstract : We have developed acid activated fluorescent probes based on amphiphilic perylene bisimide with morpholine groups on the bay (Lyso-APBI ). Incorporating one morpholine group, Lyso-APBI-1 showed an acid activated fluorescence increase of 70-fold upon pH values lowering from 8.0 to 4.0. Lyso-APBI-2, with two morpholine groups on the bay of PBI, had a red-shifted emission and a 190-fold fluorescence enhancement within same pH variation range. These Lyso-APBI probes have excellent membrane permeability, low cytotoxicity, and can rapidly accumulate and specifically activate in cell lysosomes. The double morpholine moieties make Lyso-APBI probes have higher acid activation ratio and better cell lysosome specificity. Moreover, long-time cell imaging proved the relatively high photostability of Lyso-APBI probes in a harsh physiological environment.